Beyond the article: Research needs to be published in many forms, and many media, many times along the way - Kasdorf, Bill (Information services & use, 2025)
This paper is based on the author’s presentation at the 2024 NISO Plus Global Online Conference. It makes a case not for replacing the traditional peer-reviewed article, but for the need to publish research in other forms and media throughout the research process, well before that final, formal publication. It centers on the need for researchers to communicate and collaborate with their peers effectively, and to obtain feedback from them, ideally making the research better and more useful to the research community, rather than only enshrining it in a formally peer-reviewed, published Version of Record (VOR), sometimes a year or two after the research has been completed.